Vaccine adverse events in the new millennium : is there reason for concern - Ward, B.J. (2000)
Notes that as more and more infectious agents become targets for immunization programmes, the spectrum of adverse events linked to vaccines has been widening. Concludes that this may be anticipated and avoided if the human and financial resources needed for monitoring and studying vaccine safety stay in step with the accelerating pace of vaccine development.